Traditional Chinese medicine rubia cordifolia residue and polylactic acid composite material for FDM-3D printing and preparation method and application thereof
By blending madder root residue with PLA and optimizing printing parameters, the problems of PLA material's high brittleness and poor heat resistance in FDM 3D printing were solved. This enabled the high-value utilization of medicinal herb residue and improved material performance, making it suitable for products such as biodegradable seedling containers, which aligns with the goal of green and low-carbon development.
Patent Information
- Application Number
- CN202511237181.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-01
- Publication Date
- 2025-11-14
AI Technical Summary
Existing PLA materials are brittle and have poor heat resistance in FDM 3D printing, making it difficult to meet the toughness and thermal stability requirements of medical and structural applications. At the same time, the treatment of Chinese herbal medicine residue poses environmental risks, so it is necessary to achieve high-value utilization and performance improvement.
Rubia sludge was used as a natural reinforcing phase and blended with PLA. The surface roughness and interfacial affinity of the fibers were improved by alkali treatment. The composite material was prepared by screw extrusion and the printing parameters were optimized to improve the mechanical properties and thermal stability of the material.
It realizes the high-value utilization of Chinese medicinal herb residue, improves the tensile strength, ductility and flexural modulus of PLA, has antibacterial properties, and is suitable for practical products such as biodegradable seedling containers, which is in line with the goal of green and low-carbon development.
Smart Images

Figure CN120944315A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of traditional Chinese medicine residue recycling technology, specifically relating to a composite material of Chinese medicine rubia residue and polylactic acid for FDM-3D printing. Background Technology
[0002] Developing biodegradable, green, and low-carbon novel printing materials has become a common research focus in the fields of materials science and environmental engineering. Statistics show that my country's traditional Chinese medicine industry generates tens of millions of tons of medicinal herb residue annually, which is primarily disposed of through incineration and landfill. These traditional treatment methods may trigger secondary environmental risks, including soil acidification and the emission of volatile organic compounds (VOCs), becoming a pressing issue for achieving green and low-carbon development goals. Faced with the environmental pressure brought by medicinal herb residue, a promising direction is to transform it into high-value-added green materials. This coincides with the current performance requirements of bio-based materials in the additive manufacturing field.
[0003] Meanwhile, polylactic acid (PLA), made from renewable resources such as corn and cassava, possesses compostable degradation properties and is one of the most widely used bio-based polymers in fused deposition modeling (FDM) 3D printing. However, PLA itself suffers from drawbacks such as high brittleness, poor heat resistance, and limited interlayer bonding strength, making it difficult to meet the higher requirements for toughness and thermal stability in medical and structural applications. Therefore, researchers have begun to explore using traditional Chinese medicine residue fibers as a reinforcing phase to prepare high-performance PLA composites, aiming to simultaneously achieve the dual goals of high-value utilization of waste and improvement of material performance. Summary of the Invention
[0004] Purpose of the invention: This invention uses madder root residue as a natural reinforcing phase and PLA as a matrix to construct a technical route of "root residue pretreatment - screw extrusion - FDM printing - LCA evaluation". It provides a replicable closed-loop paradigm for "resource utilization of traditional Chinese medicine solid waste - green additive manufacturing - functional product development", and also provides theoretical reference and practical model for collaborative innovation between the traditional Chinese medicine industry and the field of bio-based materials.
[0005] Technical solution: The present invention adopts the following technical solution:
[0006] A composite material of Chinese herbal medicine dregs and polylactic acid for FDM-3D printing is made by blending Chinese herbal medicine dregs and polylactic acid with a compatibilizer.
[0007] The method for preparing the composite material provided by the present invention includes the following steps:
[0008] First, the madder residue is dried, and then treated with alkali to improve the surface roughness and interfacial affinity of the fiber. Subsequently, the madder residue is mixed with PLA and a compatibilizer at a mass fraction of 5%–15%, and then the composite wire is prepared by screw extrusion.
[0009] The method for preparing the composite material described above includes the following steps:
[0010] First, the madder residue is dried at 60-70℃ and treated with 5-10% NaOH alkali to improve the surface roughness and interfacial affinity of the fiber. Then, the madder residue is mixed with PLA and compatibilizer at a mass fraction of 5%-15% and then prepared into composite wire by screw extrusion.
[0011] As a preferred embodiment, the method for preparing the composite material described above includes the following steps:
[0012] First, the madder residue was dried at 60℃ and treated with 5% NaOH alkali to improve the surface roughness and interfacial affinity of the fibers. Then, the madder residue was mixed with PLA and a compatibilizer at a mass fraction of 10%. The temperatures of the three temperature zones T1, T2 and T3 of the screw extruder barrel were set to 170℃, 180℃ and 175℃ respectively, and the screw speed was set to 18 rpm. Composite wires were prepared by screw extrusion.
[0013] Beneficial effects:
[0014] This invention first dries madder root residue at 60℃ and treats it with 5% NaOH alkali to improve fiber surface roughness and interfacial affinity. Then, the residue is blended with PLA and a compatibilizer at a mass fraction of 5%–15%, and the resulting composite filament is prepared by screw extrusion. The effect of residue content on material properties is evaluated using a TGA / DSC, melt flow index, and mechanical property testing system. Orthogonal experiments are used to optimize printing parameters (nozzle temperature, layer thickness, and printing speed). Results show that when the madder root residue content is in the range of 5–15 wt%, and the printing parameters are a nozzle temperature of 205℃, a layer thickness of 0.20 mm, and a printing speed of 220 mm / s, the printing requirements for the composite filament can be met. The optimal performance parameters are achieved at a 10% residue content, with tensile strength and ductility increasing by approximately 7 MPa and 0.7% respectively compared to pure PLA, flexural modulus increasing by 0.56 GPa, and notched impact strength increasing by 0.9 kJ / m. 2 .
[0015] By printing actual products such as biodegradable seedling containers, the feasibility of the material in agricultural applications was verified, demonstrating the circular utilization model of "value-added processing of medicinal residues - product output".
[0016] The madder residue / polylactic acid composite material has good mechanical properties, thermal stability and printing applicability, and also has certain antibacterial properties. It can realize the high-value utilization of traditional Chinese medicine residue, providing a new way to develop green and low-carbon 3D printing materials and realize the high-value utilization of medicinal residue. Attached Figure Description
[0017] Figure 1This is a schematic diagram of a 3D printed model product.
[0018] Figure 2 This is a schematic diagram of a 3D printed model product. Detailed Implementation
[0019] Example 1
[0020] 1. Experimental Materials
[0021] 1.1 Experimental Apparatus
[0022] FW-100 Traditional Chinese Medicine Pulverizer (Tianjin Taist); ODFE MK2 Small Desktop Extruder (ARTME3D); Voron 2.4 Printer (Laboratory Self-Assembled); KD-321 Electronic Balance (Bailida (Shanghai) Trading Co., Ltd.); HH-ZK1 Constant Temperature Water Bath (Nanjing Keer Instrument Equipment Co., Ltd.); R-1001VN Rotary Evaporator (Zhengzhou Changcheng Science & Industry Trade Co., Ltd.); DHG-9140A Forced Air Drying Oven (Shanghai Aozhen Instrument Manufacturing Co., Ltd.); Micrometer (Triple Measurement 211-105 Precision Type), etc.
[0023] 1.2 Reagents and Tests
[0024] Madder root residue (madder root residue after laboratory extraction with 95% alcohol and water); PLA4032D biodegradable plastic (Natureworks, USA); maleic anhydride PLA compatibilizer (Shandong Desenlai Chemical Co., Ltd.); 1010 / 168 antioxidant (Nanjing Longxiangyi Chemical Co., Ltd.); water was distilled water, and all other materials were of analytical grade.
[0025] 2. Methods and Results
[0026] 2.1 Preparation and Process Optimization of Rubia cordifolia Residue / Polylactic Acid Composite Material (RCL / PLA)
[0027] 2.1.1 Pretreatment of Rubia cordifolia residue (RCL)
[0028] Take an appropriate amount of madder root residue, dry it at 60℃ to constant weight, grind it into powder, pass it through a No. 9 sieve, and treat it with 5wt% NaOH solution at room temperature for 2 hours to remove hemicellulose and surface wax, exposing more –OH groups and enhancing interfacial adhesion with PLA. Rinse repeatedly with distilled water until the pH of the leachate is 7 to thoroughly remove residual alkaline substances and prevent PLA chain breakage during melt extrusion. Dry the neutralized residue a second time at 60℃ until the moisture content is below 2% to prevent clumping during storage and improve extrusion flowability, surface quality, and mechanical properties of the wire. The madder root residue treated in the above steps is a light brownish-red powder with good flowability.
[0029] 2.1.2 Preparation of Rubia cordifolia residue / polylactic acid composite material (RCL / PLA)
[0030] The experiment used the Original Desktop Filament Extruder MK2 (ARTME 3D) small desktop extruder. Featuring a single screw and a compact design with an L / D ratio of approximately 20:1, the device boasts three independent PID heating coils capable of stabilizing at up to 260°C. With a rated screw speed of 5–25 rpm, it can continuously extrude 0.35 kg of wire per hour. It incorporates built-in PWM traction and rewind motors, supplemented by optical diameter measurement closed-loop control, maintaining dimensional tolerances within ±0.05 mm. Based on optimized formulation and extrusion process, a complete process of "drug residue-PLA blending—melt extrusion—cooling and sizing—rewinding" is planned.
[0031] (1) Optimization of RCL / PLA formulation design: RCL was used as the base material (mass fraction in the range of 5–15 wt%), PLA4032D as the main matrix (mass fraction in the range of 82–92 wt%), 2 wt% maleic anhydride PLA compatibilizer, and 0.3 wt% antioxidant (1010 / 168 mixture). The experiment first used a single-factor method, with pure PLA as the control, and compared and analyzed the performance of extruded materials with different RCL contents (10 wt%, 15 wt%) using extruded material diameter, ellipticity, melt flow rate (MFR), and thermal weight loss rate as indicators, in order to determine the ideal RCL content range.
[0032] The results showed that, compared with pure PLA, the diameters of the three groups of samples (5wt%, 10wt%, and 15wt% residue) all met the standard of 1.75±0.05mm for pure PLA, conforming to the ASTM D1238 standard requirements for consumable diameter tolerance. In the ellipticity test, the maximum values of the three groups of samples were all 0.04mm lower than the standard value. Regarding melt flow rate (MFR), all three groups of samples were within the 3–6 g / 10min range suitable for FDM printing consumables, with the 10wt% sample exhibiting more moderate flowability. When MFR < 3 g / 10min, nozzle clogging is likely to occur, while MFR > 6 g / 10min may lead to poor interlayer adhesion. The experimental parameters in this study can simultaneously meet the needs of extrusion and printing. Thermogravimetric analysis (TGA) results showed that the weight loss rate of all three groups of samples at 250℃ / 30min was below the target upper limit of 1%, indicating that the added antioxidant played a good role in inhibiting the melt thermal degradation of PLA, especially maintaining thermal stability even at higher filler contents. The specific results are shown in Table 1.
[0033] Table 1 Comprehensive Quality Assessment
[0034]
[0035] (2) RCL / PLA extrusion process optimization: mainly includes three processes: mixing, wetting, and extrusion. RCL and PLA are dry-mixed at a constant speed for 5 minutes in a V-type mixer, and then the mixed raw materials are placed into the extruder material hopper. During the screw plasticizing stage, the material sequentially passes through three heating zones (front temperature T1, middle temperature T2, and die head temperature T3), utilizing a zoned temperature control strategy to fully melt PLA and thoroughly wet the pharmaceutical residue fibers. After screw extrusion, the melt is output, and the melt passes through… After the precision die obtains the main sizing dimensions, the internal and external temperatures are immediately balanced by room temperature air cooling at 23°C to minimize fiber settling and ellipticity deviation. Finally, the traction system stretches the cured filament at a speed ratio of 1.8:1 and feeds it into the winding machine, with the winding tension controlled within 0.18 N·m. Combined with an online optical diameter measurement system (dual 90° laser displacement meters, 2kHz sampling frequency) to monitor the diameter in real time, this ensures that the final wound composite filament meets the requirements of high-precision FDM printing consumables.
[0036] Since zoned temperature control and screw speed are key parameters affecting material extrusion, the experiment first optimized the temperatures of the three barrel temperature zones (T1, T2, T3) using a single-factor method, with radial deviation and melt flow rate (MFR) of the composite filament as indicators. It was found that the radial deviation was minimized (±0.037 mm) and the MFR was approximately 4.5 g / 10 min at a combination of 170 / 180 / 175 °C. Simultaneously, the experiment investigated the effect of different screw speeds (12–22 rpm) on material properties. The results showed that below 10 rpm, fiber dispersion was insufficient and the composite strength decreased by approximately 8%; above 22 rpm, increased barrel back pressure easily led to melt pulsation and filament diameter fluctuations. Therefore, an 18 rpm screw speed was selected, which achieved a stable yield of approximately 0.22 kg / h on the extruder while controlling filament diameter fluctuations within ±0.05 mm. The results are shown in Table 2.
[0037] Table 2 Single-factor screw speed experiment
[0038]
[0039]
[0040] 2.2 Design of Printing Parameters and Performance Testing of Rubia cordifolia Residue / Polylactic Acid Composite Material (RCL / PLA)
[0041] Subsequently, standard samples were prepared based on the optimal combination, and the mechanical, thermal stability, and functional (hygroscopic slow-release, compostable and degradable) properties were systematically tested. A regression model was then used to analyze the synergistic relationship between "drug residue content - printing parameters - performance." This provides a reusable paradigm for parameter design and performance evaluation of functionalized bio-based composite materials in high-speed FDM scenarios.
[0042] 2.2.1 Optimization of printing parameters
[0043] Based on the fabrication of RCL / PLA composite filaments, a Voron 2.4 printer was used. An orthogonal experimental design was employed to optimize key parameters affecting printing performance, such as nozzle temperature (205–225℃), layer thickness (0.1–0.3 mm), and printing speed (120–300 mm / s) (Table 3). Nozzle temperature affects interlayer bonding strength and dimensional accuracy; layer thickness was examined to assess the trade-off between thinner layers improving delamination adhesion (≤0.15 mm significantly enhances adhesion) and thicker layers improving printing speed (≥0.30 mm accelerates molding), as well as their impact on surface finish; printing speed was used to explore the balance between melt stability and interlayer shear strength (ASTM D732) under high-speed extrusion conditions. When the speed exceeded 250 mm / s, PLA was prone to stringing or poor adhesion.
[0044] Table 3 Printing Parameter Experiment
[0045] level T / ℃ h / mm <![CDATA[v / mms -1 ]]> 1 205 0.1 120 2 215 0.2 220 3 225 0.3 300
[0046] The experimental results are shown in Table 4. The results were obtained by adjusting the nozzle temperature (T), layer thickness (h), and printing speed (v) at L9(3) 3 Range and variance analyses were performed on the interlayer shear strength data from orthogonal experiments to reveal the dominant role and contribution rate of each factor on the strength of the printed part. The results showed that the influence of each factor was in the order T>h>v, and the influence of different levels from largest to smallest was T1>T2>T3, h1>h2>h3, and v2>v3>v1; therefore, the optimal printing process was initially determined to be T1h1v2. Variance analysis (Table 5) showed that the effects of nozzle temperature (T) and layer thickness (h) were statistically significant (P<0.05), while the printing speed (v) was not statistically significant (P>0.05). This suggests that extrusion or nozzle temperature, by regulating melt flowability and grain recrystallization behavior, becomes a key factor determining the mechanical properties of the final molded part. In summary, a nozzle temperature of 205℃ and a layer thickness of 0.20mm are proposed as the preferred combination for 3D printing to maximize interlayer bond strength while maintaining good printing efficiency.
[0047] Table 4. Results of L9 Orthogonal Experiment
[0048] Test No. T(℃) h(mm) <![CDATA[v(mms -1 )]]> Interlaminar shear strength σILSS (MPa) 1 205 0.1 120 28 2 205 0.2 220 29 3 205 0.3 300 26 4 215 0.1 220 25 5 215 0.2 300 24 6 215 0.3 120 22 7 225 0.1 300 21 8 225 0.2 120 20 9 225 0.3 220 18 <![CDATA[K1]]> 83 74 70 <![CDATA[K2]]> 71 73 72 <![CDATA[K3]]> 59 66 71 R 24 8 2
[0049] Table 5. Analysis of Variance (ANOVA)
[0050] Source of mutation sum of squares df Mean Square F P Contribution rate / % Nozzle temperature / T 96 2 48 144 0.007 87.27 Layer thickness / h 12.67 2 6.33 19 0.049 11.52 speed / v 0.67 2 0.33 1 0.5 0.61 residual 0.67 2 0.33 — — 0.61 total 110.01 8 — — — 100
[0051] 2.2.2 Mechanical and thermal performance testing
[0052] Using orthogonally optimized printing parameters (nozzle temperature 205℃, layer thickness 0.20mm, printing speed 220mm / s) on a Voron 2.4 printer, ASTM D638-IV, D790-A, and ISO 179-1eA standard specimens were printed on pure PLA and composite filaments with different madder residue contents (5%, 10%, and 15%). Tensile, bending, notched impact, dynamic thermomechanical (DMA), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA) were then performed. All specimens were placed at 23±2℃ and 50±5%RH for 48 hours to eliminate the influence of humidity on the test results. Specific parameters are shown in Table 6.
[0053] Table 6 Sample preparation and testing methods
[0054] Performance indicators Spline size / standard Instruments and conditions Purpose and Explanation Tensile strength, elongation ASTM D638-IV Instron5967 Evaluation of collaborative carrying capacity Flexural modulus ASTMD790-A <![CDATA[Same as above, 2mm min - 1]]> Comparison of stiffness improvement amplitude Notched impact strength ISO179-1eA, Notch 2 Zwick / 5113,2.9J Testing brittleness improvement DMA <![CDATA[-40→120℃,2℃min - 1]]> TA-Q800 Measurement of glass transition line DSC -50→200℃,10℃ TA-Q2000 Measurement of Tg, Tm and crystallization TGA 30→600℃,10℃ TA-Q500 JudgmentTonset
[0055] (1) Mechanical property testing: Tensile tests and flexural performance evaluations were conducted using pure PLA as a reference. The average tensile strength of pure PLA was 54 MPa, and the elongation after fracture was 4.6%. With the increase of RCL residue content, especially in the range of 10%-15%, the strength and ductility of the composite material were significantly improved (P<0.05). When the residue proportion increased to 15%, the tensile strength and elongation decreased slightly. In terms of flexural performance, the flexural modulus of pure PLA was 2.94 GPa, and the notched impact strength was 3.2 kJ / m. 2 At a 10% RCL content, the balance between stiffness and toughness is optimal, and the impact strength is maximized (4.1 kJ / m). 2 Compared to pure PLA, the yield was improved by approximately 28%. This indicates that madder fibers pretreated with NaOH, under the action of PLA-g-MAH compatibilizer, can form a microcrack energy-dissipating network in the matrix, thereby enhancing the impact resistance of the composite material. The results are shown in Table 7.
[0056] Table 7 Mechanical property results
[0057] Material Tensile strength / MPa Elongation / % Flexural modulus / GPa <![CDATA[Izod impact / kJm -2 > Pure PLA 54±1 4.6±0.3 2.94±0.05 3.2±0.3 5% RCL 58±1* 4.9±0.2 3.30±0.04 3.6±0.2 10% RCL 61±2* 5.3±0.4* 3.50±0.03* 4.1±0.2* 15% RCL 59±2* 5.0±0.3* 3.42±0.05* 3.8±0.3*
[0058] (2) DMA Analysis: Based on the mechanical property test results, DMA analysis was performed using pure PLA as a reference. The results showed that the storage modulus E′ of the 10% RCL group was about 18% higher than that of pure PLA throughout the glassy state range (-20→40℃), and the peak value of tanδ was slightly lower than that of pure PLA and shifted to the lower temperature direction by 1.5℃, indicating that the improvement of interfacial bonding strength reduced the relaxation loss of molecular chains. The results are shown in Table 8.
[0059] Table 8 Results of Dynamic Thermomechanical Analysis
[0060]
[0061]
[0062] (3) DSC and crystallization behavior: The results showed that the cold crystallization peak of the 10% RCL group was significantly enhanced, the crystallinity increased from 9% of pure PLA to 14%, and the glass transition temperature decreased slightly from 58℃ to 55–56℃, mainly attributed to the plasticizing effect of trace amounts of TBC; the melting peak T m Maintaining a temperature around 169℃ indicates that the residue did not alter the crystal structure of PLA. The results are shown in Table 9.
[0063] Table 9: DSC and Crystallization Behavior Results
[0064] parameter PLA 10% RCL Tg / ℃ 58 55–56 Cold crystallization peak Tcc / ℃ 113 106 Melting peak Tm / ℃ 169 169 <![CDATA[ΔHc / Jg -1 ]]> 24.1 33.2 <![CDATA[ΔHm / Jg -1 ]]> 18.3 23.1 Crystallinity Xc / % 9 14
[0065] (4) TGA analysis: The results showed that the initial decomposition temperature (Tonset) of the 10% RCL group increased to 332℃ (8℃ higher than that of pure PLA). max The temperature also increased from 361℃ to 366℃. This suggests that the residual mineral ash and phenolic hydroxyl structures in the residue have an inhibitory effect on free radical amplification at high temperatures, while the synergistic inhibitory effect of antioxidants and TBC further enhances thermal stability. The results are shown in Table 10.
[0066] Table 10 Thermogravimetric Analysis Data
[0067] sample Tonset (5% wt) / °C <![CDATA[T max / ℃]]> Pure PLA 324 361 5% RCL 329 364 10% RCL 332 366 15% RCL 331 365
[0068] 2.2.3 Functional Verification
[0069] (1) Antibacterial activity: In the agar diffusion antibacterial test, pure PLA showed almost no inhibition zone (<1 mm), while with the increase of the amount of residue added, the RCL-PLA composite material showed inhibition zone diameters of not less than 5 mm against Escherichia coli and Staphylococcus aureus, indicating that the prepared composite material had excellent antibacterial activity. Compared with PLA composite antibacterial films containing silver and zinc oxides, this system can achieve an inhibition diameter of >8 mm against E. coli without additional inorganic additives. The results are shown in Table 11.
[0070] Table 11 Antibacterial activity data
[0071]
[0072]
[0073] (2) Moisture absorption performance: In a constant humidity environment of 25±1℃ and 75±2%RH, the printed optimized composite rectangular sample (60×10×2mm) was placed on a capillary balance. After recording the initial mass m0, the wet weight m was read every 24 hours. tThe moisture absorption rate will continue to increase until it reaches near saturation after 72 hours. The moisture absorption rate can be calculated using the following formula: M t =(m t -m0) / m0×100%. The results showed that the moisture absorption rate of pure PLA was only 1.6% under the conditions of 25℃ / 75%RH / 72h, while the moisture absorption rate of 10% RCL wire reached 4.1%. It is speculated that the porous structure of the fiber itself and the hydrophilic hydroxyl groups significantly enhance the material's affinity for moisture. The results are shown in Table 12.
[0074] Table 12 Moisture Absorption Performance Data
[0075] Sample 0h / % 24h / % 48h / % 72h / % Pure PLA 0 0.8±0.1 1.2±0.1 1.6±0.1 5% RCL 0 2.0±0.1 3.1±0.2 3.8±0.2 10% RCL 0 2.4±0.1 3.5±0.2 4.1±0.2 15% RCL 0 2.6±0.2 3.7±0.2 4.4±0.3
[0076] 2.3 Product Development Based on Rubia cordifolia Residue / Polylactic Acid Composite Material (RCL / PLA)
[0077] The experiment focuses on two directions: biodegradable seedling containers and cultural and creative products based on traditional Chinese medicine. It aims to transform madder root residue-PLA composite filaments into 3D printed models with antibacterial, slow-release, and rapid degradation properties.
[0078] 2.3.1 Biodegradable seedling containers
[0079] (1) Structure and Modeling: The container structure uses a honeycomb perforated wall as the main load-bearing and ventilation unit. A regular hexagonal honeycomb grid with a wall thickness of 2mm and an aperture of 10mm was constructed using SolidWorks software. Compared to a solid wall design, the honeycomb unit can increase the porosity by approximately 38% without significantly sacrificing mechanical rigidity, thus optimizing the flow efficiency of air and moisture. The cross-bracing beams inside the honeycomb are arranged in a grid pattern along both 45° and –45° directions, forming multi-directional force channels. A nested tapered structure is designed between the outer and inner walls of the container: the container's top diameter is 60mm, bottom diameter is 50mm, and the taper angle is approximately 5°, allowing multiple containers to be tightly stacked when unloaded. Figure 1 ).
[0080] (2) Printing and Post-processing: Using optimal printing parameters (nozzle temperature 205℃, layer thickness 0.24mm, and printing speed 200mm / s) and a high-flow nozzle, a single model was printed in approximately 40 minutes. During the printing process, the low-temperature plasticizing formula effectively protected the color of the anthraquinone natural pigments in madder, allowing the finished product to maintain a warm reddish-brown texture even under high-flow-rate printing. After printing, the surface of the finished product was lightly sanded with 600-grit sandpaper to remove fine burrs and layer line protrusions, preserving the natural fiber texture while avoiding color loss or structural weakening due to excessive abrasion. The final product has a slightly uneven surface and a natural visual effect, combining functionality and aesthetics. Figure 2 ).
[0081] (3) Product performance evaluation: The ultimate compressive load of the product was determined according to the method in ISO 178 "Plastics - Determination of flexural properties"; the water saturation rate of the product after 24 hours was determined according to the method in ASTM D570. The results showed that, compared with pure PLA printed products, the ultimate compressive load of the biodegradable seedling container printed with 10% RCL-PLA composite material increased from 220N to 255N, and the saturation water absorption rate after 24 hours increased from 1.2% to 3.5%.
[0082] (4) Rapid degradation tracking: After the seedling containers were buried in outdoor soil for 6 months, cracks began to appear on the surface of the containers in the 3rd month. In the 6th month, the residual mass was only about 38%, indicating that the fiber filler significantly promoted water penetration and microbial erosion, and accelerated the decomposition of the material. This shows that the composite material can be effectively applied to biodegradable seedling containers, which meets the needs of agricultural production for "integrated use of seedling planting-transplanting-degradation".
[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A composite material of Chinese medicinal herb madder root residue and polylactic acid for FDM-3D printing, characterized in that, It is made by blending the residue of the Chinese herbal medicine Rubia cordifolia, polylactic acid, and a compatibilizer.
2. The method for preparing the composite material according to claim 1, characterized in that, Includes the following steps: First, the madder residue is dried, and then treated with alkali to improve the surface roughness and interfacial affinity of the fiber. Subsequently, the madder residue is mixed with PLA and a compatibilizer at a mass fraction of 5%–15%, and then the composite wire is prepared by screw extrusion.
3. The method for preparing the composite material according to claim 2, characterized in that, Includes the following steps: First, the madder residue is dried at 60–70℃ and treated with 5–10% NaOH alkali to improve the surface roughness and interfacial affinity of the fiber. Then, the madder residue is mixed with PLA and compatibilizer at a mass fraction of 5%–15% and then prepared into composite wire by screw extrusion.
4. The method for preparing the composite material according to claim 3, characterized in that, Includes the following steps: First, the madder residue was dried at 60℃ and treated with 5% NaOH alkali to improve the surface roughness and interfacial affinity of the fiber. Then, the madder residue was mixed with PLA and compatibilizer at a mass fraction of 10%. The temperatures of the three temperature zones T1, T2 and T3 of the screw extruder were set to 170℃, 180℃ and 175℃ respectively, and the screw speed was set to 18 rpm. Composite wire was prepared by screw extrusion.
5. The application of the composite material according to any one of claims 1 to 4 in FDM-3D printing materials.
6. The application according to claim 5, characterized in that, During FDM-3D printing, the nozzle temperature was 205 ℃ and the layer thickness was set to 0.20 mm.
7. The use of the composite material according to any one of claims 1 to 4 in the preparation of antibacterial materials.
8. The application of the composite material according to any one of claims 1 to 4 in the preparation of 3D printed models with antibacterial, sustained-release and rapid degradation properties.
